Iridium‐Catalyzed Hydrogen Production from Monosaccharides, Disaccharide, Cellulose, and Lignocellulose. Issue 5 (6th February 2015) - Li, Yang; Sponholz, Peter; Nielsen, Martin; Junge, Henrik; Beller, Matthias
Abstract Hydrogen constitutes an important feedstock for clean‐energy technologies as well as for production of bulk and fine chemicals. Hence, the development of novel processes to convert easily available biomass into H2 is of general interest. Herein, we demonstrate a one‐pot protocol hydrogen generation from monosaccharides, disaccharide, and extremely demanding cellulose and lignocellulose substrates by using a pincer‐type iridium catalyst. Applying ppm amounts of this catalyst, hydrogen is produced at temperatures lower than 120 °C. More specifically, catalyst turnover numbers (TONs) for lignocellulose from bamboo reached up to about 3000. Interestingly, even (used) cigarette filters, which are composed of cellulose acetate, produce hydrogen under optimized conditions.